2014
DOI: 10.1016/j.cattod.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Ti(III)APO-5 materials as selective catalysts for the allylic oxidation of cyclohexene: Effect of Ti source and Ti content

Abstract: TON values higher than 200 after 6 h of reaction at 343 K and higher than 550 after 24 h. The interest of Ti(III)APO-5 catalysts lies on their high selectivity to products formed through allylic oxidation of cyclohexene. The main product of this reaction, 2cyclohexenyl hydroperoxide, was obtained with more than 80 % selectivity over Ti(III)APO-5 catalysts. This behavior is in contrast with the well-known strong tendency of the more active Ti-zeolites to epoxidize the double bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…would fall within the experimental error of the electron microscope. Despite the experimental impossibility of assuring the existence of structural deformation, the incorporation of Ti into the P and Al sites would be in good agreement with the conclusion reached by combining indirect characterization techniques in these TAPO materials prepared with Ti III sources as well as their redox catalytic behavior . In Figure b the simulated structure is presented, in which Ti replaced all P atoms, using a crystal thickness of 10 nm.…”
Section: Resultssupporting
confidence: 72%
“…would fall within the experimental error of the electron microscope. Despite the experimental impossibility of assuring the existence of structural deformation, the incorporation of Ti into the P and Al sites would be in good agreement with the conclusion reached by combining indirect characterization techniques in these TAPO materials prepared with Ti III sources as well as their redox catalytic behavior . In Figure b the simulated structure is presented, in which Ti replaced all P atoms, using a crystal thickness of 10 nm.…”
Section: Resultssupporting
confidence: 72%
“…In this sense, the activity of Ti‐MCM‐41 catalysts in the epoxidation of alkanes is weakened if anhydrous TBHP becomes hydrated 28. As a second possible reason, water acts as an inhibitor in the oxidation of cyclohexene through the radical route,24a, b which dominates over the epoxidation route under the tested conditions. Finally, this radical route requires the homolytic rupture of the OO bond of the peroxide, which has been calculated to be more unfavorable for H 2 O 2 than for TBHP in the presence of a Ni‐based catalyst 29…”
Section: Resultsmentioning
confidence: 99%
“…The versatility covers a large number of solvents,22 all M of the series of M–MOF‐74 (except Zn, taken as reference) already tested in the reaction,17b, 23 two different oxidation routes24 (Scheme ), and different oxidizing agents 25. Acetonitrile was selected as the solvent because it is one of the most widely used in cyclohexene oxidation and it is able to dissolve all reactants in a unique liquid phase even if 30 wt % H 2 O 2 in aqueous solution was used as the oxidant 24b…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently reported that the AFI-type materials obtained by using this synthesis strategy are efficient catalysts for the oxidation of cyclohexene with either hydrogen peroxide or tert-butylhydroperoxide as oxidants. These catalysts show a very high selectivity to the allylic oxidation of this cyclic olefin [28,29], a reaction pathway quite different to the oxidation of the double bond to form the corresponding epoxide so characteristic of Ti-zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…This work reports the synthesis procedure of several Ti-containing materials with the AFI topology from gels containing Ti(III), and their physico-chemical characterization, in order to assess the effective incorporation of this metal into the framework and to shed light on the nature of the generated Ti centers, which showed unusual catalytic behavior in the oxidation of cyclohexene [28,29]. wt.…”
Section: Introductionmentioning
confidence: 99%